Hearing God : developing a conversational relationship with God - Willard, Dallas, (Dallas Albert), 1935- (Downers Grove, IL : IVP Books, 1999)
"God spoke to me." "The Spirit spoke to my heart." "God revealed the idea to me." Being close to God means communicating with him -- telling him what is on our hearts in prayer and hearing and understanding what he is saying to us. It is this second half of our conversation with God that is so important but that can also be so difficult. How do we hear his voice? How can we be sure that what we think we hear is not our own subconscious? What role does the Bible play? What if what God says to us is not clear? The key, says best-selling author Dallas Willard, is to focus not so much on individual actions and decisions as on building our personal relationship with our Creator. In this updated and expanded edition of Willard's beloved book, originally published as In Search of Guidance, you'll gain rich spiritual insight into how we can hear God's voice clearly and develop an intimate partnership with him in the work of his kingdom. Including new material from Dallas Willard's teaching at the Renovare Institute and reformatted to be even easier to read, this classic continues to endure as one of today's best resources for learning to listen closely to God. - Publisher.
Preface -- A paradox about hearing God -- Guidelines for hearing from God -- Never alone -- Our communicating cosmos -- The still, small voice and its rival -- Redemption through the Word of God -- Recognizing the voice of God -- A life more than guidance -- Epilogue : The way of the burning heart.
Includes bibliographical references (p. [296]-302) and index.
Keywords: Spiritual life -- Christianity; God (Christianity) -- Will